2012
DOI: 10.1002/cbdv.201100092
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Secondary Metabolites of a Pseudoalteromonas sp. Isolated from Sediments Collected at the Northeastern Coast of Brazil

Abstract: Continuing search for anticancer compounds from the marine environment, we have studied microorganisms that inhabit intertidal sediments of the northeastern Brazilian coast. Of the 32 strains isolated, 13 were selected for biological evaluation of their crude extracts. The acetate extract obtained from a Gram-negative bacterium was strongly active against cancer cell lines with IC(50) values that ranged from 0.04 (HL60 leukemia cells) to 0.26 μg/ml (MDA MB-435 melanoma cells). The bacterium was identified as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Concerning Pseudoalteromonas bacterium found in this work in both sponges, it produces as secondary metabolite the prodigiosin, a well-known tripyrrole red pigment with immunosuppressive and anticancer activities, mainly in human breast cancer [15]. Also Proteobacteria species, that we found associated with G. cydonium , resulted widespread in the marine environment.…”
Section: Resultsmentioning
confidence: 66%
“…Concerning Pseudoalteromonas bacterium found in this work in both sponges, it produces as secondary metabolite the prodigiosin, a well-known tripyrrole red pigment with immunosuppressive and anticancer activities, mainly in human breast cancer [15]. Also Proteobacteria species, that we found associated with G. cydonium , resulted widespread in the marine environment.…”
Section: Resultsmentioning
confidence: 66%
“…Our recent results showed that a diverse assemblage of bacteria resided in the marine sponge G. cydonium [ 27 ], including Pseudoalteromonas spp. that is reported to produce prodigiosin, a well-known tripyrrolic red pigment with immunosuppressive and anticancer activities, mainly in human breast cancer [ 28 ]. However, to our knowledge, this is the first study testing the biological activity of extracts of this sponge.…”
Section: Resultsmentioning
confidence: 99%
“…BRA007 (M23), a strain obtained from Taíba Beach, Ceará state. This study described the cytotoxicity of prodigiosin in a 4-tumor cell line panel and, remarkably, a nearly 100-fold selectivity towards a human breast epithelial cell line, HB4a, stably transfected with cDNA for the receptor tyrosine kinase ErbB-2, in comparison to the parental cell line [139]. Prodigiosin, which is known to induce apoptosis in cancer cells through an intricate, multi-target but not fully characterized mechanism, has been shown to reduce GSK-3β/NAG-1 [140] and JNK/p38/RAD51 [141], as well as to downregulate the expression of members of the IAP family of proteins (▶ Fig.…”
Section: Further Accessing Brazilian Marine Environments: Studies Witmentioning
confidence: 99%